Greenhouse gas balance associated with sugarcane production in South-Central Brazil, considering the management and expansion - Bordonal, Ricardo de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The substitution of fossil fuel with sugarcane ethanol aiming to reduce emissions of greenhouse gases (GHGs) has recently been debated because of the possible emissions incurred from land use change (LUC). This work was based on GHG inventory from cultivation and LUC of recently established sugarcane plantation in south-central Brazil, with the purpose of estimating the impact of expansion on GHG balance, including emissions and removals due to LUC. Changes in quantity and quality of soil carbon (C) upon conversion of diverse agricultural systems (coffee, citrus, annual crops and pasture) to sugarcane in southern Brazil were also assessed through field experiments. The estimates show that sugarcane cultivation and its expansion during 2006-2011 in south-central Brazil presented an overall accumulated GHG balance of 217.1 Tg CO2eq by 2030, including emissions from cultivation activities and emissions/removals due to LUC. Expansion of sugarcane plantation contributed to attenuate part of GHG emissions from agricultural production phase. Similarly, the ethanol C offset by displacing fossil fuels could readily payback that C deficit. The data obtained by field experiments show that the LUC of coffee and citrus to sugarcane depleted soil C stock by 21.5% (26.8 Mg C ha-1) and 23.6% (34.9 Mg C ha-1) in the 0-100 cm layer after a period of 3 and 4 years, respectively. In contrast, there was no significant difference in soil C stocks in 0-100 cm depth upon conversion of pasture and annual crop into sugarcane. However, only the conversion of pasture into sugarcane decreased soil C stock in 0-20 cm depth, with depletion of 13.3 Mg C ha-1 (43.9%) over 8 years after the LUC. With regard to the quality of soil C, the data of Laser-Induced Fluorescence Spectroscopy (LIFS) showed that the higher the losses of soil C, the greater was the humification index (HLIFS) of soil organic matter (SOM). In general, conversion of the agrosystems (e.g., coffee, citrus, annual crop and pasture) into sugarcane increased HLIFS of SOM. For some depths, HLIFS more than doubled in comparison with the previous land uses. We expect that the results achieved in this work may contribute to the development of actions and public policies to strengthen strategies for GHG mitigation and ensure the environmental benefits of sugarcane ethanol in Brazil.

A substituição dos combustíveis fósseis pelo etanol de cana-de-açúcar visando à redução das emissões de gases de efeito estufa (GEE) tem sido recentemente questionada devido às possíveis emissões decorrentes da mudança do uso da terra (MUT). Este trabalho se baseou no inventário de GEE do cultivo e da MUT associada à expansão da cana-de-açúcar no centro-sul do Brasil, com a finalidade de estimar o impacto dessa expansão no balanço de GEE, incluindo as emissões e remoções devido à MUT. Objetivou-se também, por meio de experimento de campo, avaliar as mudanças na quantidade e qualidade do carbono (C) do solo após a conversão de diferentes agrossistemas (café, citros, cultura anual e pastagem) para cana-de-açúcar no sudeste do Brasil. As estimativas apontam que o cultivo da cana-de-açúcar e sua expansão durante 2006-2011 no centro-sul do Brasil resultaram no balanço acumulado total de GEE de 217,1 Tg CO2eq em 2030, incluindo as emissões das atividades de cultivo e as emissões/remoções associadas à MUT. As estimativas indicam que a expansão dos canaviais contribuiu para atenuar parte das emissões de GEE da fase de produção agrícola. Do mesmo modo, o uso de etanol em substituição aos combustíveis fósseis poderia facilmente compensar esse déficit de C. Os resultados das avaliações de campo apontam que a conversão de café para cana-de-açúcar resultou na depleção dos estoques de C do solo de 21,5% (26.8 Mg C ha-1) e 23,6% (34.9 Mg C ha-1) na camada de 0-100 cm ao longo dos períodos de 3 e 4 anos após a MUT, respectivamente. As conversões de pastagem e cultura anual para cana-de-açúcar não apresentaram diferenças significativas na camada de 0-100 cm. Entretanto, apenas a transição de pastagem para cana apresentou diferenças significativas na camada de 0-20 cm, resultando na depleção dos estoques de C do solo de 43,9% (13.3 Mg C ha-1) durante 8 anos após a conversão. Com relação à qualidade do C do solo, a técnica de espectroscopia de fluorescência induzida por laser mostrou que quanto maior a perda de C no solo devido à MUT para cana, maior o índice de humificação (HFIL) da matéria orgânica do solo (MOS). Em geral, a conversão dos agrossistemas (café, citros, cultura anual e pastagem) para cana-de-açúcar promoveu o aumento do HFIL da MOS. Em algumas profundidades, o HFIL mais do que dobrou em relação aos usos anteriores. Espera-se que os resultados gerados neste trabalho contribuam para o desenvolvimento de ações e políticas públicas visando fortalecer estratégias que possam potencializar ainda mais a mitigação de GEE, e garantir os benefícios ambientais do etanol de cana-de-açúcar no Brasil.
Balanço de gases de efeito estufa associado à produção de cana-de-açúcar no centro-sul do brasil, considerando-se o manejo e a expansão
Keywords: Ethanol production; Inventory; Land use change; Mitigation; Sugarcane management; Climate change; Produção de etanol; Inventário; Mudança do uso da terra; Mitigação; Manejo da cana-de-açúcar; Mudanças climáticas